Language Education in Primary School and Language Teacher Cognition. Some Results from a Survey in Lombardy - SOLERTI, PAOLA (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2021)
Italy has always been characterised by a multilingualism that, in addition to Italian and its varieties, includes a very large number of dialects and several historical minority languages. The Italian school, on the other hand, has long, with rare exceptions, been a monolingual institution. Over the last fifty years, internationalisation and globalisation, the growing demand for foreign language learning, and continental and intercontinental migrations (which have introduced an unprecedented neo-multilingualism into Italian society in terms of the number of varieties and types of languages involved), have presented schools with new and even greater challenges. At around the same time, a vision of language education as a comprehensive and unitary process unfolding across the curriculum and encompassing the teaching/learning of the mother tongue, the language of instruction, foreign languages and classical languages has been emerging in the theoretical field. The implementation of language education is, however, ultimately entrusted to teachers and is therefore strongly influenced by teachers’ knowledge, beliefs, implicit theories, opinions, attitudes and, in general, by everything that falls within the definition of teacher cognition. This contribution presents the results of a broader survey, conducted in 2018 in Lombardy through the administration of a questionnaire. The data presented allow us to explore the language teacher cognition of primary school teachers with respect to different aspects of language education